MANAJEMEN KURIKULUM KULLIYATU-L-MU’ALLIMIN AL-ISLAMIYAH DI PONDOK MODERN AL MUJAHIDUL AMIN PALANGKA RAYA - Putri, Cindy Marcellina; Ahmadi, Ahmadi; Hikmah, Nurul (STKIP Pesisir Selatan, 2025)
This study aims to analyze and describe the curriculum management of Kulliyatu-l-Mu'allimin Al-Islamiyah (KMI) at Pondok Modern Al Mujahidul Amin Palangka Raya, focusing on three main aspects, namely planning, organizing, and implementing the curriculum. This study uses a qualitative approach with a case study type conducted from March to November 2025. Data were obtained through participatory observation, in-depth interviews with boarding school leaders, and documentation studies of official curriculum documents. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana, which includes the processes of condensation, presentation, and drawing conclusions. The results of the study show that curriculum planning is carried out by adopting the KMI Pondok Modern Darussalam Gontor system, which is based on spiritual legitimacy and the basic values of Islam, Indonesianness, and pesantren (Islamic boarding school). In the early stages, the boarding school did not conduct its own needs analysis because it focused on preserving the values and traditions of Gontor education, but it remained open to adjustments in line with local developments and needs. The curriculum is organized into three main subject groups, namely Dirāsah Islāmiyyah, Dirāsah Lughawiyyah, and Dirāsah Kauniyyah, with an integrated 24-hour learning system.